Effect of two percent turmeric extract gel on minor recurrent aphthous stomatitis - N., Nurdiana; Krishnasamy, Shamini (Padjadjaran Journal of Dentistry, 2016)
Minor recurrent aphthous stomatitis (RAS) is recurrent oral ulcer with clinical features of shallow ulcer, round or oval shape, measuring less than 10 mm, covered with yellowish white pseudomembrane and surrounded by erythematous halo. Inflammation and pain that accompany the RAS make individual seek treatment to relieve these symptoms. Turmeric extract gel is a traditional medicine that can be used to cure RAS because it has anti-inflammatory, antibacterial, covering agents and antioxidants effect. The aim of this study was to explore the effect of 2% turmeric extract gel on minor RAS in reduction of erythematous halo, ulcer size, and pain intensity. This study was an experimental study using a pre test – post test control group design. The study involved 16 patients with minor RAS at University of Sumatera Utara Dental Hospital. Data collected by initial examination of RAS which included erythematous halo, ulcer size and pain intensity then controlled every day for the next three days. Analysis of the data in this study was used Friedman Test and Wilcoxon Signed Ranks Test to determine the difference between observations before and after RAS treatment. This study showed statistically significant results in reduction of erythematous halo at day of examination to first control with P value of 0.03 and first control to second control with P value of 0.025. Reduction of ulcer size showed statistically significant result at day of examination, first, second and third control with P value of 0.001 (P < 0.05). This study also showed statistically significant reduction in pain intensity with P value of 0.001 (P < 0.05) for day of examination to first control and first control to second control, as well as 0.014 (P < 0.05) for second control to third control. The results of this study showed a significant reduction in erythematous halo, ulcer size, and pain intensity.